Preparation of high self-healing efficient crosslink HTPB adhesive for improving debonding of propellant interface. (4th November 2020) - Tu, Jing; Xu, Heng; Liang, Li; Li, Pingyun; Guo, Xiaode
Abstract : A high self-healing efficient HTPB-based adhesive containing disulfide bonds, which can improve propellant interface debonding defects at a safe temperature. Abstract : The problem of debonding the interface between propellant grain and propellant coating has been a tricky problem that has puzzled many scholars. Self-healing adhesives are expected to solve this problem. Herein, we studied the most widely used HTPB system in composite propellants. By adopting free radical polymerized HTPB as the soft segment of the adhesive and introducing aromatic disulfides, we successfully prepared a self-healing polyurethane adhesive. The adhesive can self-heal at a safe temperature of 80 °C, with an elongation at break of more than 700% and a self-healing efficiency of up to 97%, and has excellent thermal stability. The interface self-healing experiment showed that the adhesive can recover the debonding damage at the interface. Our results will provide a new insight into the rebonding of the interface between propellant grain and coating.